Automatic run-time versioning for BPEL processes - Melo, P.; Rupino da Cunha, P.; Ferreira da Silva, C.; Macedo, A. (Service Oriented Computing and Applications, 2017)
We describe a middleware solution for automatic run-time process versioning in Business Process Execution Language (BPEL) and then analyse its impact in terms of scalability and performance. Business processes change in response to business needs, but the deployment of new versions to a BPEL engine must ensure that running instances are not disrupted and can conclude following their original workflows. Our solution is implemented as a standalone component that manages versioning transparently to the process editor, the orchestration engine, the web services used by the process, and the end-user. We have tested it for almost 1 year in the production environment of a telecommunications company, without significant overhead in terms of process invocation time.